PELATIHAN PUBLIC SPEAKING PADA SISWA - SISWI SMKN 1 KAYANGAN KABUPATEN LOMBOK UTARA - Sandi Justitia Putra; I Made Putra Suryantara; L. Ahmad Rahmat; Irma El-Mira Husbuyanti; Zulhadi; Ismi Arifiana Rahmandari; Denda Devi Sarah Mandini (Puslitbang Sekawan Institute Nusa Tenggara, 2023)
Public speaking skills training for students at SMKN 1 Kahyangan, North Lombok Regency. Community Service (PkM) is an effort by a service team to contribute science and technology to society and especially in this case with students. Based on this, the team submitted a proposal for PkM activities in state schools located in North Lombok Regency. The aim of this PkM is to provide basic skill training related to public speaking. This training is expected to provide provisions for students about the benefits of practicing public speaking and is also beneficial for the development of knowledge possessed by students and solving problems related to errors in speaking. The output target of this activity is that the trainees are equipped with public speaking and video recordings of students speaking in front of the camera.